(untitled) (Journal of the Bangladesh Agricultural University, 2020)
Soil salinity is a serious abiotic stress which restricts the crop growth in saline soil. In spite of having huge effort globally, still there is a limited success in developing technology for sustainable saline soil management. The present experiment aimed at reducing the detrimental effect of salt on crops by judicious use of K fertilizer in saline soils. The experiment was carried out during rabi season of 2017 in farmers’ field of Tajepara village of Kalapara upazila under Patuakhali district, Bangladesh. It was laid out in a randomized complete block design with three replications, each plot size being 5 × 3 m. There were nine treatments, namely control or K omission (T1), next four treatments consisting of 100% recommended K fertilizer dose (RKFD) (T2), 125% RKFD (T3), 150% RKFD (T4) and 175% RKFD (T5) which were applied as basal; another four treatments having 100% RKFD (T6), 125% RKFD (T7), 150% RKFD (T8) and 175% RKFD (T9) applied in two equal splits- one half as basal and one half at 55 days after sowing. The test crop was maize and the variety was ACI Hybrid maize (Don 111). The results revealed that salinity mostly affected reproductive growth, not vegetative growth. Application of K fertilizer significantly reduced the deleterious effect of soil salinity. The K fertilizer recommendation (100% RKFD) as outlined in FRG-2012 was found insufficient, a 25 % higher rate was found as the best for achieving higher yield of maize in saline soil. Split application (half basal+half at 55 DAS) of K was found better than single basal application. The 125% rate of K application is therefore recommended for growing maize in coastal saline soils of Bangladesh. J Bangladesh Agril Univ 18(2): 362–366, 2020 https://doi.org/10.5455/JBAU.76119